DIGITAL UZBEKISTAN - 2030 STRATEGY, DIGITAL LITERACY AND THEIR EFFECTIVE MEASURES - Alimova E’zoza Ne’matillayevna; Nurmatova Nasibaxon Xoshimjanovna (Bright Mind Publishing, 2025)
In this article, it is highlighted on measures to approve the strategy of "Digital Uzbekistan - 2030", to use digital technologies in various fields, the development of digital technologies, to develop the system of education and improve the education system through an analytical opinion.
Keywords: Digital technologies,